Revisiting the Application of the Ten Year General Period of Limitation: Judicial Discretion to Disregard Art 1845 of the Civil Code - Eshetu, Andualem Lema (Bahir Dar University Journal of Law, 2022)
The period of ten year stipulated in Article 1845 of the Civil Code is widely accepted as a General Period of Limitation (GPoL) and is often applied to all civilclaims irrespective of the origin and nature of obligations unless a special period of limitation has been fixed by law. However, due to the absence of a clear ruleregarding the dimension and scope of its application, the general applicability of Article 1845 has been contested on different occasions. Thus, this article examines the issue of whether the period of ten year is appropriate for all civil claims or not. while assessing the instances where such GPoL could be disregarded by the discretion of the court under the guidance of certain considerations. Accordingly, it canvasses the issue of whether the court should always apply the ten year GPoL by the mere fact that the law provides neither a special period of limitation nor exclusionary rule, or ought there be a little room where the court may apply some other period of limitation to other similar claims by analogy; or exempt certain claims from the subject of limitation before the move to apply Article 1845 of the Civil Code, which is explicitly stipulated for contractual claims. This article concludes that even though the argument advocating for the general application of the ten-year period in the absence of special periods of limitation is a widely shared view, the door should not be totally closed for judicial discretion whereby the period maybe disregarded on the basis of different considerations. However, since the reliance on judicial discretion to override a limitation period would render the law too uncertain, the author maintains that Ethiopia should adopt a separate and relatively comprehensive statute of limitation that clearly provides, inter alia, the dimension and scope of application of the ten year GPoL and lists of claims exempted from the subject of limitation to avoid the misuse of Article 1845 of the Civil Code.